LOCUS OF CONTROL IN LATE ADOLESCENCE: CHARACTERISTICS AND ABILITY OF NEW STUDENTS TO OVERCOME DEPRESSION - Hidayat, Ade; Sahrudin, Asep (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
The aim of this study is to uncover and gain some factual data about locus of control (LOC) ability to overcome depression in late adolescence. This study was conducted through survey methods on new under-graduate students aged 18 to 21 years old from English Education program in Mathla’ul Anwar University of Banten at first semester of academic year 2015-2016. The result of study showed that majority of the students has internal LOC. The sudents who have external LOC tend to get more depressed than those who pose internal LOC. The numbers of women who get depressed are more than men. The finding also showed positive influence of reading book in gaining capacity of LOC. Depression can be avoided and prevented by spiritual and mental strengthening, such as being closer to God, spending quality time with parents, siblings and friends, doing some new hobbies and activities, getting involved in fun daily activities, and trying to identify sense of fear of being rejected or guilty feelings.